False positive blood culture from automated microbial detection system in severe malaria – a case report - Mohd Rahim, Syarifah; Masri, Siti Norbaya; Ibrahim, Rosni (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Automated microbial detection system (AMDs) are design to detect early growth of bacterial and fungal. We herein report a rare case of false positive blood culture by AMDs in Plasmodium falciparum infection. A 41-year-old previously healthy lady, with recent history of travelling to Lagos, Nigeria had presented to the casualty with history of fever and lethargy for three days. There was no malaria prophylaxis taken prior to the travelling history. Peripheral blood smear confirmed the presence of young trophozoite of Plasmodium falciparum with parasitemia of 7%. Concurrent blood culture sent was positive, however all subcultures were negative for any growth. She was treated with intravenous artesunate however succumbed to death on the day of admission due to severe falciparum infection complicated with multiorgan failure and shock. The aim of this report is to highlight, the circumstances that can trigger the false positive AMDs detection and the possible underlying mechanism.